GREEN CHEMISTRY PRACTICAL GUIDE INTEGRATING THE CONCEPTS OF SCIENCE LITERACY AND ENVIRONMENTAL AWARENESS - Vindhy Dian Pratika; Faudina Permatasari; Pharaye Gintano (JURNAL PENA SAINS, 2025)
Science education at the elementary school level has an important role in forming the basis of scientific knowledge while fostering character values, including environmental awareness. The background of this research is based on the need for science learning that not only emphasizes cognitive aspects, but also forms an environmentally conscious character from an early age. This research aims to develop a practical guide and see the feasibility of the guide with the theme of Green Chemistry that integrates the concept of scientific literacy and environmental awareness, which is intended for fifth grade elementary school students. The research method used is research and development (RD) with the 4D development model (Define, Design, Develop, and Disseminate). The results of the study indicate that the development of a Green Chemistry practical guide that integrates scientific literacy and environmental awareness is declared very feasible to be developed. The results of the development of the practical guide from the validation results of material experts showed that 87% were declared very feasible, the results of the validation results of media experts produced a feasibility percentage of 84% in the very feasible category, and the results of the practicality of the readability by students of the practical guide showed an average result of 82.40% which stated very feasible. Thus, this practical guide can be used by teachers and students as a source of independent learning that can increase environmental awareness.